A DYADIC EXAMINATION OF INSPIRATIONAL FACTORS DRIVING B2B SOCIAL MEDIA INFLUENCE. Issue 1 (3rd April 2018) - Barry, James M.; Gironda, John
Abstract : This study demonstrates how digital content, engagement strategies, and influence tactics inspire social media communities to embrace B2B marketers seeking their advocacy. Using grounded theory in the context of transformational and charismatic leadership, a model is proposed for examining a marketer's capacity to inspire. Along with its proposed antecedents and outcomes, inspirational motivation was tested on a dyad of 171 influencer/content evaluators. Results confirmed that inspirational motivation drives social media influence. Inspirational motivation, in turn, is directly influenced by humor, visionary insights, and engagement. Results also showed support for the mediating influence humor has on visual storytelling and inspirational motivation.